Reading, Writing And Walking: Student Projects Linking Primary Documents, Classroom Learning, And Historical Sites - Reeve, Kay (Teaching History: A Journal of Methods, 2000)
Virtually every instructor who teaches history survey courses has struggled with issues of time constraint at one time or another. Choices between sufficient content coverage, in-depth analysis of crucial issues, connections with broader concepts and themes, and opportunities to encourage critical thinking and analysis appear to be rivals for limited time on both the part of the student and instructor. I encountered this issue in an intensified manner in 1991 when I came to Kennesaw State University. The college recently had redesigned its general education core curriculum to include two courses in world history and two courses in United States history configured with the "typical" chronological divisions, but had reduced each course in credit hours and, concurrently, classroom contact time. I found myself having one-third less in class time with my students as well as needing to adhere to reasonable limitations on out-of-class requirements.